A reinvenção do sertão: organização social e poder na comunidade do Belo Monte (Canudos, 1893-1897) - Martins, Paulo Emílio Matos (1999)
From june 1893 to october 1897, the Belo Monte community (Canudos, BA,Brazil), under Antônio Conselheiro's leadership, experienced an approximately 10,335% demographic growth in the most arid region of the caatinga' and resisted for 10 months to a disproportionate war effort imposed by almost half (49.8%) of the brazilian Army contingent of that time, supported by many battalions of the military public forces, of the state of Amazonas, Bahia, Pará and São Paulo, under the command of tive generais, the elite of the terrestrial national force and, at the end of the conflict, under the command of the war minister himself, marshal Carlos Machado Bittencourt. Through the recognition of this episode as a very expressrve adrninistrative phenomenon, despite of its tragic destiny, this thesis studies the organizational models and power/authority that made possible the growth, supply and defense of Canudos in such a criticai situation. Under the perspective of an institutional understanding of the social imagery about the episode, this study proposes an analysis model denominated Organizational Semiologic Tetrahedron and compares statements by descends of the war survivors with reports by chronicler-witnesses', studious of the subject, iconographic, musicographic and literary registry over the episode.